2021
DOI: 10.1055/s-0041-1732370
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Muscle Hematoma in Patients with COVID-19: A Systematic Literature Review with Description of an Additional Case Series

Abstract: Coagulation abnormalities, thrombosis, and endothelial dysfunction have been described in COVID-19 patients. Spontaneous muscle hematoma (SMH) is a rare complication in COVID-19. The aims of this study are to: (1) perform a systematic review of the literature to better define the clinical SMH characteristics, (2) describe the prevalence and the clinical characteristics of SMH in COVID-19 patients referring to a Department of Internal Medicine (IM) (Federico II University of Naples), a Department of Sub-Intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 49 publications
1
20
0
3
Order By: Relevance
“…Coronavirus disease 2019 (COVID-19) is a novel coronavirus infection characterized by severe complications, such as arterial and venous thrombotic events, and a high mortality rate [1][2][3][4]. Coagulopathy and a pro-thrombotic state, with high D-dimer and fibrinogen levels, are reported widely in hospitalized COVID-19 patients and are related to high mortality [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) is a novel coronavirus infection characterized by severe complications, such as arterial and venous thrombotic events, and a high mortality rate [1][2][3][4]. Coagulopathy and a pro-thrombotic state, with high D-dimer and fibrinogen levels, are reported widely in hospitalized COVID-19 patients and are related to high mortality [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19–related coagulopathy resulting in spontaneous MSK hemorrhage is much less common than thromboembolism. Spontaneous bleeding most commonly occurs in skeletal muscle, especially the iliopsoas, as well as the pectoralis major and rectus abdominis muscles ( 41 , 42 ). A recent study showed that critically ill COVID-19 patients were twice as likely to develop a spontaneous iliopsoas hematoma compared with those in the intensive care unit for other reasons ( 41 ).…”
Section: Covid-19 In Msk Systemmentioning
confidence: 99%
“…Anticoagulation therapy is the biggest risk factor for developing spontaneous muscle hematoma. Other risk factors include older age, obesity, hypertension, and diabetes mellitus ( 42 ). Several proposed mechanisms may contribute to the pathogenesis of this phenomenon, including prophylactic anticoagulation therapy and renal damage–associated decreased clearance of anticoagulants.…”
Section: Covid-19 In Msk Systemmentioning
confidence: 99%
“…In the same vein, spontaneous hematomas developed in patients suffering or recovering from COVID-19 were rarely described [7,14], being mostly associated with the treatment with LMWH [1,9,11]. According to the guidelines, LMWH are the treatment of choice for patients with deep vein thrombosis (DVT), and are also used as prophylaxis in COVID-19 [15][16][17]. This therapy should be initiated as soon as possible after establishing the diagnosis to prevent DVT and life-threatening complications, especially pulmonary embolisms (PEs) [1,3,18].…”
Section: Introductionmentioning
confidence: 99%